Analisis Pemberdayaan Ibu dalam Melakukan Skrining Perkembangan Anak Mengggunakan Buku KIA (Kesehatan Ibu dan Anak) - Hardianty Nurul Fadyah; Rita Yulifah; Dwi Yuliawati (STIKES Columbia Asia Medan, 2025)
In toddlerhood, child development is an important period (golden age), because at that time there is a basic development that runs rapidly so that it can influence and determine the child's future development. The use of the KIA (Maternal and Child Health) book by parents of toddlers in stimulating child development has not been implemented optimally. The purpose of this study was to analyze the empowerment and skills of mothers in conducting child development screening using the KIA (Maternal and Child Health) book at Kartika IV - 41 Kindergarten and Melati 1 PAUD Post, Kesatrian Village, Malang City. The research design used descriptive analytic with a cross-sectional approach, sampling technique using purposive sampling with a total of 77 respondents who had children attending Kartika IV - 41 Kindergarten and Melati PAUD Post. Data collection using a maternal empowerment questionnaire and a skills observation sheet. The results of the statistical test using the Spearman Rank test showed that the ρ value was (0.000). The proposed research hypothesis is an alternative hypothesis, where, Ha: ρ ≠ 0. Which shows that maternal empowerment contributes to maternal skills in conducting independent child development screening using the KIA book for children attending PAUD Melati 1 Post and Kartika IV – 41 Kindergarten, Kesatrian Village, Malang City.